Tipos de abonos orgánicos en aspectos agronómicos de Brassica juncea L. Mostaza de hoja, Loreto.2024 - Ruiz Sanchez, Nena Alexandra (2025)
The research was carried out in the Loreto Region in a terrain with textural characteristics of clay loam, of low fertility, with medium content of organic matter whose purpose was to analyze the effects on Leaf Mustard (Brassica juncea L.) of 3 types of organic years: Poultry Manure (T4), Compost of Household Organic Solid Waste (T3), Compost of Compound Organic Matter (T2) and a control treatment without application of Organic Fertilizer (T1). Statistical design was used to study the results. of the BCA, Tukey's Test that led to important conclusions: Manure (T4) turned out to be the most effective organic fertilizer than the other organic fertilizers, promoting greater vegetative development and yield as can be seen in the results of 900 g per plant and 45,000 Kg/ha and an economic utility of S/.20,428.00.